Analisis Studi Kelayakan Bisnis Pemasaran Obat Herbal Madu Ditinjau dari Aspek Pasar dan Pemasaran - Setiawan, Puji; Supriyatno, Dedi; K, Afni Sodja; S, Andri Mei; Situmorang, Klinton; B, Wisnu Yudha; T, Satria Primagus; Auliya, Iqbal; Hayat, Maulana (Proceeding Mercu Buana Conference on Industrial Engineering, 2025)
The purpose of this research is to assess the business feasibility and to increase sales of "Neo Herbamart Store" Herbal Honey, located in North Cikarang, as a micro, small, and medium enterprise (MSME), with a focus on market and marketing aspects. Using a qualitative descriptive approach, this study analyzes market and marketing aspects. The results of the study indicate that Trigona Herbal Honey has met the legal requirements by having a halal certificate, which supports legitimate and sustainable operations. From a production perspective, this business is located in a strategic location, namely close to residential areas that help with business operations, using quality materials, and implementing a regular production process, so it is feasible for further development. In terms of market and marketing, there is promising potential with a focus on consumers who have stomach complaints and marketing strategies through social media. This study recommends that Trigona Herbal Honey increase product variations and expand distribution channels, including collaborating with pharmacies by utilizing digital marketing, to increase competitiveness and its contribution to the local economy.